Investigation of mental workload and job satisfaction among officer workers at a selected electronic company / Nor Qistina Md Ali - Nor Qistina, Md Ali (2020)
This study investigated the level of mental workload and job satisfaction among office workers at a selected electronic company in Subang Jaya. 103 professional workers from various departments comprising 54 males and 49 females participated in this study. DASS-21, Carga Mental Questionnaire, and Job Satisfaction Survey were used to gather data from the participants. Socio-demographic data were collected from participants too. The results showed mental workloads level is low among the workers while the level of job satisfaction is average. However, the level of stress among female workers is mild which is slightly higher than males. There are significant correlations between age of workers and mental workloads (CarMen-Q) based on statistical analysis. The age of workers positively correlates with performance demands, cognitive demands, and emotional demands in this organization except for temporal demands. The relationship between job satisfaction and mental workloads was evaluated using SPSS software to find the correlations. Additionally, there are opportunities for improvement by top management to conduct campaigns and programs to increase awareness on mental health and to review current job grade, compensation and benefits packages for improvement of job satisfaction (related to promotion, operating conditions, contingent rewards, and fringe benefits).